Reader Engagement with Third-Generation Electronic Literature: An Affective Stylistic Study of Instapoetry - Chouia Nour; Hadj Ali Safa (University of El-Oued, 2025)
الملخص: يلاقي شعر انستغرام اليوم اقبالا و اهتماما كبيرين من طرف مستخدمي منصة انستغرام، وهذا ما أدى الى ازدهار الشعر في الآونة الأخيرة. الهدف من هذه الدراسة هو استكشاف مدى تأثير الخصائص الاسلوبية على تفاعل القراء، وذلك بالاعتماد على نظرية الأسلوبية العاطفية لمعرفة كيف لشعر الانستغرام ان يؤثر على القراء بشكل عاطفي وذهني وتشاركي. وبالإضافة الى ذلك فإن هذه الدراسة تعالج فجوة نقص البحوث الادبية في ما يتعلق بتفاعل القراء مع شعر انستغرام، وذلك للتوصل إلى رؤى حول هذا التفاعل الفريد الذي يحدث في إطار الجيل الثالث للأدب الالكتروني. ولقد تم تطبيق في هذه الدراسة دراسة حالة تتضمن اساليب للتحليل الكمية منها والنوعية في إطار صغير مختارات شعرية كتبت من طرف شاعرتين هما نيكيتا جيل ولانق ليف .أشارت النتائج الكمية إلى أن استخدام خاصية الريلز في الشعر واختيار المواضيع الحساسة يجذبان بشكل ملحوظ تفاعلًا أكبر من القراء، ويتجلى ذلك في مقاييس التفاعل: الإعجابات، والمشاركات، والتعليقات. علاوة على ذلك، كشفت النتائج النوعية أن السمات الأسلوبية تؤثر على استجابات القراء وتساعد على خلق تجربة قراءة غامرة من خلال تشجيعهم على التفاعل بطريقة عاطفية ومعرفية وتشاركية مع القصائد. كما تُظهر النتائج مساهمة كبيرة في هذا المجال، إذ تقدم رؤى قيّمة حول الاستجابات التشاركية. وهذا يشمل التفاعل بين القارئ والشاعر، وكذلك بين القراء أنفسهم، أثناء مشاركتهم في عملية صياغة المعنى. ويسترشد هذا ويتأثر بالسمات الأسلوبية المضمنة في القصيدة. في النهاية، تقدم الرؤى المستخلصة من هذه الدراسة تطبيقات عملية محتملة، حيث يمكن أن تساعد نتائجها الأساتذة المختصين في الأدب والحضارة على تعزيز تفاعل الطلاب مع هذا النوع الأدبي، وأن تكون بمثابة دليل لدمج الأدب الرقمي في أساليب التعليم المستقبلية. Abstract : This study aims to explore how Instapoetry affects readers’ responses by employing affective stylistics theory to investigate the emotional, cognitive, and participatory responses to selected Instapoems. The study addresses a critical gap in literature regarding readers’ response to third generation electronic literature. To achieve this, the research employs a case study design and utilises quantitative and qualitative methods of analysis, focusing on small scale selection of poems by two instapoets, Nikita Gill and Lang Leav. The quantitative findings indicated the use of reels and the selection of sensitive themes significantly tend to attract higher readers engagement, manifested by engagement metrics: likes, shares, and comments. Further, the qualitative analysis revealed that Instapoetry style affects readers' responses and invites different reactions, including emotional, cognitive and participatory ones. Additionally, the findings showcase a significant contribution to affective stylistics through the exploration of participatory responses. This involves interaction between the readers and the poet, as well as among readers themselves, as they engage in the process of co-creating the meaning. This is guided and influenced by the stylistic features embedded in the poem. Ultimately, the insights gained from this study offers potential theoretical implications to affective stylistics, as its findings can help literature and civilisation educators to enhance student engagement with this genre of literature and serve as a guide for incorporating digital literature into future educational methods.
Master's Degree In Literature and Civilization
Keywords: الأسلوبية العاطفية، شعر الانستغرام، لانڨ ليف، نيكيتا جيل، الجيل الثالث للأدب الالكتروني; Affective Stylistics; Instapoetry; Lang Leav; Nikita Gill; Third-Generation Electronic Literature.